2020
DOI: 10.1177/1534735420911430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Holothurian Glycosaminoglycan on the Sensitivity of Lung Cancer to Chemotherapy

Abstract: Sea cucumber is a kind of food. Holothurian glycosaminoglycan (hGAG) is extracted from the body wall of the sea cucumber. Administration of hGAG and cisplatin (DDP) together to treat lung cancer was investigated. Lung adenocarcinoma A549 cells were cultured and divided into 4 groups: control group, hGAG 100 µg/mL group, DDP 3 µg/mL group, and hGAG 100 µg/mL + DDP 3 µg/mL group. Cell inhibition and apoptosis was evaluated by CCK8 and Hoechst33258 staining. Cell cycle was tested by Annexin V-FITC/PI (propidium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Kaori haneji et al extracted a sulfated polysaccharide fucoidan from brown algae Cladosiphon okamuranus Tokida and found that it induced tumor cell apoptosis in two different leukemia cell lines [122]. Cunzhi Lin et al found that the holothurian GAG extracted from the body wall of sea cucumber can promote the apoptosis of lung adenocarcinoma A549 cells and inhibit the proliferation of A549 cells [123]. Further studies showed that GAG could promote cell cycle arrest in G1 and G2 phases and improve the chemotherapeutic effect of cisplatin on A549 cells [123].…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Kaori haneji et al extracted a sulfated polysaccharide fucoidan from brown algae Cladosiphon okamuranus Tokida and found that it induced tumor cell apoptosis in two different leukemia cell lines [122]. Cunzhi Lin et al found that the holothurian GAG extracted from the body wall of sea cucumber can promote the apoptosis of lung adenocarcinoma A549 cells and inhibit the proliferation of A549 cells [123]. Further studies showed that GAG could promote cell cycle arrest in G1 and G2 phases and improve the chemotherapeutic effect of cisplatin on A549 cells [123].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Cunzhi Lin et al found that the holothurian GAG extracted from the body wall of sea cucumber can promote the apoptosis of lung adenocarcinoma A549 cells and inhibit the proliferation of A549 cells [123]. Further studies showed that GAG could promote cell cycle arrest in G1 and G2 phases and improve the chemotherapeutic effect of cisplatin on A549 cells [123].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…A proper amount of complete culture medium was added into each well, and cells were incubated for 24 hours. As for the concentration of hGAG, we referred to our previous study, 19 in which it was found that concentration at 100 µg/ml of 3W and 5W hGAG did not show any cytotoxicity to the cancer cells and showed the most obvious effect compared with other concentrations. Cells were divided into 6 groups: control group; 3W molecular weight hGAG therapy group (the concentration of hGAG was 100 μg/ml); 5W molecular weight hGAG group (the concentration of hGAG was 100 μg/ml); HPD-PDT group (hematoporphyrin derivative concentration was 8 μg/ml and cells were irradiated by a 630 nm laser; in the process, the laser energy density was 50 mW/cm 2 , the spot diameter was about 9 cm, the irradiation time was 2 minutes and the vertical distance between the emitter and the 96-well plate was 9 cm.…”
Section: Methodsmentioning
confidence: 99%
“… 18 Moreover, a previous study of our research group has confirmed that hGAG can strengthen the sensitivities of tumor cells to chemotherapy. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Sea cucumbers (or holothurians), a classic traditional Chinese medicine, have been used in traditional medicine practices for thousands of years in China and many other countries in Asia. They have an impressive character of valuable nutrients, including triterpene glycosides (saponins) [12][13][14][15][16], chondroitin sulfates, glycosaminoglycan [17] and peptides [18] that are recognized as the origin of unique biological and pharmacological functions of sea cucumbers, including anti-angiogenesis [19], anti-coagulation [20], anti-bacterial [21], antiinflammatory [18,22,23], anti-diabetic [24], and anti-cancer [12,15,16,19,25,26]. Among the approximately 21 species of edible sea cucumber in China, with the exception of the Apostichopus japonicus, all are tropical species.…”
Section: Introductionmentioning
confidence: 99%